Inside Back Cover: Observation of Diastereomeric Interconversions of β‐Sulfinylsubporphyrins as Evidence for Bowl Inversion (Chem. Eur. J. 33/2015). Issue 33 (3rd August 2015) - Yoshida, Kota; Osuka, Atsuhiro
<x xml:space="preserve">Abstract</x> Subporphyrins B‐Methoxy and B‐phenyl β‐sulfinylsubporphyrins have been separated into their diastereomers and their diastereomeric interconversions have been studied in various solvents, as reported by K. Yoshida and A. Osuka in their Full Paper on page 11727 ff. Diastereomeric interconversion of B‐methoxy subporphyrin diastereomers takes place in protic solvents as the first experimental observation of bowl inversion of a subporphyrin, which likely proceeds by an SN1‐type mechanism via a subporphyrin borenium cation.